Optimal cycle slip detection and correction with reliability. Issue 349 (3rd July 2016) - Wang, Z.; Wang, X.; Ji, S.; Chen, W.
Abstract : Cycle slip detection and correction is very important for high-precision positioning with GNSS. In past research, a lot of work has been done on this subject, especially for current dual-frequency GPS (the global positioning system). However, few have been done about the reliability. Similarly to ambiguity resolution, reliability is important to cycle slip detection and correction. In this research work, methods on how to assess and ensure the reliability of cycle slip detection and correction are proposed.